Efficient time slot assignment algorithms for TDM hierarchical and nonhierarchical switching systems. - Yeung, K.L (IEEE Transactions on communications)
Two efficient time slot assignment algorithms, called the two-phase algorithm for the nonhierarchical and the three-phase algorithm for the hierarchical time-division multiplex (TDM) switching systems, are proposed. The simple idea behind these two algorithms is to schedule the traffic on the critical lines/trunks of a traffic matrix first. The time complexities of these two algorithms are found to be O(LN2) and O(LM2), where L is the frame length, N is the switch size, and M is the number of input/output users connected to a hierarchical TDM switch. Unlike conventional algorithms, they are fast, iterative and simple for hardware implementation. Since no backtracking is used, pipelined packet transmission and packet scheduling can be performed for reducing the scheduling complexity of a transmission matrix to O(N2) and O(M2), respectively. Extensive simulations reveal that the two proposed algorithms give close-to-optimal performance under various traffic conditions